OPTIMALISASI PERAN LEMBAGA MEDIASI DALAM PENYELESAIAN SENGKETA WARIS ISLAM - Sukrisno, Heru; Renanggal; Dwi Kurnia, Martina; Santosa; Enggarty Nafebi, Yovensy; Mul Erowati, Eti (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
Mediation is an effective alternative method for resolving Islamic inheritance disputes peacefully and in accordance with Sharia. This study analyzes the roles, challenges, and optimization strategies of mediation within the context of Islamic inheritance law. Using a qualitative approach based on document analysis and literature review, the findings reveal that mediation holds significant potential to reduce conflicts but faces obstacles in regulation, mediator competence, and cultural factors. Optimization strategies include mediator training, regulatory enhancement, and public education. This research contributes to the development of mediation as a harmonious solution for inheritance disputes.